The Role Women Farmer’s Group (KWT) In Economic Empowerment of Batu Kambing Village, Pasaman District - Esilvita, Esilvita; Setiawati, Setiawati (Universitas Negeri Padang, 2023)
Agriculture is part of national economic development which is based on efforts to create a prosperous, just and prosperous Indonesian society as mandated in the 1945 Constitution. To improve the economy in the agricultural sector, one thing that can be done is to form a Women's Farmers Group (KWT). The existence of KWT shows that women can also be active in agricultural activities and there is no difference from men. The method used in this research is descriptive which describes the research results but does not produce broader conclusions. Data collection techniques were obtained from observations, interviews and documentation. The object of research in this research is the Women's Farmers Group (KWT) which consists of 2 groups, namely KWT Tuah Sepakat which has 25 members and KWT Banjar Padang Sepakat which has 29 members. The existence of KWT in Batu Kambing provides real results, where farmers are able to manage their yards or yards into land for growing vegetables or secondary crops. Apart from that, it can help the family's economy because their farming results can be used for daily needs and can even be sold to other people.